Flexible Bismuth Selenide /Graphene composite paper for lithium-ion batteries. Issue 1 (January 2017) - Chen, Xinhang; Tang, Hongli; Huang, Zongyu; Zhou, Jie; Ren, Xiaohui; Huang, Kai; Qi, Xiang; Zhong, Jianxin
Abstract: A flexible Bi2 Se3 /Graphene (BSG) composite paper has been prepared through a simple vacuum filtration method and a thermal reduction together. The BSG composite paper was directly used as anode electrode for lithium-ion batteries, without using any polymer binders or conduction additives. In contrast to the pure Bi2 Se3, the BSG exhibits high reversible lithium ion storage capacities and superior cyclic capacity retention. It proposed that the superior lithium storage performances would be attributed to the special construction of the as-prepared BSG paper, in which the graphene can not only act as conductive network for electrodes, but also act as a frame to alleviate volume expansion or aggregation of Bi2 Se3 nanosheets during lithiation/delithiation. The as-prepared BSG paper shows a great potential as an anode materials for flexible Li-ion batteries.